Bell's palsy in a case of Darier's disease - a rare disease association or coincidental finding? - Kritika Pandey; Mankesh Lal Gambhir; Suresh Kumar Malhotra (Our Dermatology Online, 2016)
Darier's disease (DD) is a rare acantholytic dyskeratotic autosomal dominant genodermatosis characterized by the presence of warty, brown papules and plaques affecting the seborrhoeic areas. Frequent bacterial, fungal and viral particularly herpes simplex virus (HSV) infections complicate DD. Bell's palsy is an acute onset, idiopathic facial paralysis resulting from a dysfunction anywhere along the peripheral part of the facial nerve. Reactivation of HSV is considered to be the main cause of Bell's palsy. This case represents, to the best of our knowledge, the first case of DD presenting with Bell's palsy. This case underlines the importance of recognizing HSV infection in DD.